The Analysis of Meanings and Forms in The A.T. Mahmud’s Song Lyrics - Ekaningrum, Prastiana; Suharto, Suharto (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2015)
The purpose of this study is to describe the analysis of meanings in the A.T. Mahmud’s song lyrics. This research used the approach of music compositions and the language approach in semantics to find out the meanings of the lyrics. This research used content analysis techniques. The analysis includes two aspects; they are: (1) the analysis of the meanings of the song lyrics based on the language aspects; and (2) the analysis based on the aspects of the music compositions. The songs to be analyzed are Bintang Kejora, Pelangi, and Cicak. The lyrics of these songs indicate that in the process of creation, Mahmud focused on the beauty of the language, such as the diction, figure of speech, rhyme, and repetition. The songs use children words that correspond to the child's development, so that children understand and memorize easily. The songs created by A.T. Mahmud are mostly about daily life; the suitable themes for children’s characteristics and world. Based on the analysis in the music compositions, most of the songs form two parts and each part of the song consists of two phrases or sentences.